Mobile app to promote Singapore's hawker food culture - Tan, Dave Chun Ann (Nanyang Technological University, 2024)
This report details the journey of creating an educational mobile application aimed at educating and promoting the uniquely Singapore’s hawker food culture spanning from requirement gathering to the development phase. The project is developed with the use of Android Studio and incorporating various essential core services such as Firebase.